Analisis Pidato Kajian Retorika Aristoteles pada YouTube Video Perayaan Wisuda Virtual - Pramesthi, Jasmine Alya (CV. ITTC INDONESIA, 2023)
The state of COVID-19 that occurs in almost all parts of the world has made various activities carried out virtually from home in accordance with government policies. With all the activities done from home will cause several mental health problems. In order to provide support to the community, especially 2020 graduates who failed to celebrate graduation face-to-face, YouTube on June 7, 2020 broadcasts original content directly to carry out virtual graduation celebrations to congratulate, convey enthusiasm and inspiration to graduates with the title